Convalescent Plasma Therapy in Severe-Critical COVID-19 Patients at North Kalimantan Regional Public Hospital: Survival Analysis. - Isnuwardana, Ronny; Pusvita Dewi, Ni Putu Merlynda; Firdausi, Fitri; Pertiwi, Ayu Putri; Cahyasit, Fortragina Tarakondiorie; Karim Parinding, Azlansa Abdul; Putro, Fikri Samodro; Rahman, Tesa Iswa; ., Maikel (Gaceta Médica de Caracas, 2022)
Background: Convalescent plasma therapy (CPT) is one of the methods used in treatment in COVID-19, but the administration of CPT to COVID-19 patients is still controversial. This study aims to assess the difference in survival between CPT administration in severe-critical COVID-19 patients and standard therapy. Methods: This research was a retrospective cohort observational research. Survival analysis was carried out on the factor and outcome variables by estimating the median survival time and Kaplan-Meier survival curve.